Targeting the crosstalk of epigenetic modifications and immune evasion in nasopharyngeal cancer - Looi, Chin King; Foong, Lian Chee; Chung, Felicia Fei Lei *; Khoo, Alan Soo Beng; Loo, Ee Mun; Leong, Chee Onn; Mai, Chun Wai (Springer, 2023)
Nasopharyngeal carcinoma (NPC) is a distinct type of head and neck cancer that is highly associated with Epstein-Barr virus (EBV) infection. EBV acts as an epigenetic driver in NPC tumorigenesis, reprogramming the viral and host epigenomes to regulate viral latent gene expression, and creating an environment conducive to the malignant transformation of nasopharyngeal epithelial cells. Targeting epigenetic mechanisms in pre-clinical studies has been shown promise in eradicating tumours and overcoming immune resistance in some solid tumours. However, its efficacy in NPC remains inclusive due to the complex nature of this cancer. In this review, we provide an updated understanding of the roles of epigenetic factors in regulating EBV latent gene expression and promoting NPC progression. We also explore the crosstalk between epigenetic mechanisms and immune evasion in NPC. Particularly, we discuss the potential roles of DNA methyltransferase (DNMT) and histone deacetylase (HDAC) inhibitors in reversing immune suppression and augmenting antitumour immunity. Furthermore, we highlight the advantages of combining epigenetic therapy and immune checkpoint inhibitor to reverse immune resistance and improve clinical outcomes. Epigenetic drugs have the potential to modulate both epigenetic mediators and immune factors involved in NPC. However, further research is needed to fully comprehend the diverse range of epigenetic modifications in NPC. A deeper understanding of the crosstalk between epigenetic mechanisms and immune evasion during NPC progression is crucial for the development of more effective treatments for this challenging disease.